Analisis Efek Organizational Citizenship Behavior dan Komunikasi Organisasi Terhadap Stres Kerja - Andreanus Pungkas Rubiyandono (Jurnal Akuntansi Bisnis, 2019)
Abstract Basically Organizational Communication should have an effect on work stress, but from the results of previous research shows that it is inversely proportional to the existing concept. Therefore, the researcher conducted additional mediation variabels that would examine the relationship between organizational communication and work stress, namely Organizational Citizenship Behavior (OCB) which was reviewed by Perception of Quality of Interaction Interaction - Subordinate. Organizations with employees who have good OCB will have better performance than other organizations. The researcher was interested in examining the influence of Organizational Communication on Job Stress in manufacturing companies in the city of Semarang with the role of Organizational Citizenship Behavior (OCB) which was viewed by Perceptions of the Quality of Interaction of Superiors and Subordinates as mediators. The result shows that organizational communication is an individual perception of communication conducted by superiors in job descriptions, commitment and coordination to subordinates does not affect the individual's perception of interpersonal relations in terms of willingness to help without coercion between superiors and subordinates. This happens because companies already have a culture that directly makes employees or employees in the work environment willing to help, not willing to help because of the interaction process in that environment. So from that the role of Organizational Citizenship Behavior (OCB) reviewed by Perception of Quality Interaction - Subordinate has not become a mediator in the relationship of Organizational Communication to Job Stress. Abstrak Pada dasarnya Komunikasi Organisasi seharusnya memiliki efek terhadap stress kerja, namun dari hasil riset terdahulu tidak konsisten dengan konsep yang ada. Maka dari itu penelitian ini melakukan penambahan variabel mediasi yang akan mengkaji hubungan antara komunikasi organisasi dengan stress kerja yaitu Organizational Citizenship Behavior (OCB) yang ditinjau Persepsi Kualitas Interaksi Atasan – Bawahan. Organisasi dengan karyawan yang memiliki OCB yang baik, akan memiliki kinerja yang lebih baik dari organisasi lain. Peneliti tertarik untuk meneliti pengaruh Komunikasi Organisasi terhadap Stres Kerja pada perusahaan manufaktur di kota Semarang dengan peran Organizational Citizenship Behavior (OCB) yang ditinjau Persepsi Kualitas Interaksi Atasan dan Bawahan sebagai mediator. Hasilnya menunjukan komunikasi organisasi merupakan persepsi individu terhadap komunikasi yang dilakukan oleh atasan dalam deskripsi pekerjaan, komitmen maupun koordinasi kepada bawahan tidak berpengaruh terhadap persepsi individu tentang hubungan interpersonal dalam hal kerelaan membantu tanpa adanya paksaan diantara atasan dan bawahan. Hal tersebut terjadi dikarenakan perusahaan sudah memiliki budaya yang secara langsung membuat pegawai atau karyawan dalam lingkungan kerja tersebut bersikap rela membantu, bukan sikap rela membantu yang dikarenakan proses interaksi dalam lingkungan tersebut. Pada dasarnya Komunikasi Organisasi seharusnya memiliki efek terhadap stress kerja, namun dari hasil riset terdahulu tidak konsisten dengan konsep yang ada. Maka dari itu peran Organizational Citizenship Behavior (OCB) yang ditinjau Persepsi Kualitas Interaksi Atasan – Bawahan belum menjadi mediator dalam hubungan Komunikasi Organisasi terhadap Stres Kerja.